Predictive value of hypothermic machine perfusion parameters combined perfusate biomarkers in deceased donor kidney transplantation. Issue 2 (20th January 2022) - Qiao, Yuxi; Ding, Chenguang; Li, Yang; Tian, Xiaohui; Tian, Puxun; Ding, Xiaoming; Xiang, Heli; Zheng, Jin; Xue, Wujun
Abstract: Background: Delayed graft function (DGF) is the main cause of renal function failure after kidney transplantation. This study aims at investigating the value of hypothermic machine perfusion (HMP) parameters combined with perfusate biomarkers on predicting DGF and the time of renal function recovery after deceased donor (DD) kidney transplantation. Methods: HMP parameters, perfusate biomarkers and baseline characteristics of 113 DD kidney transplantations from January 1, 2019 to August 31, 2019 in the First Affiliated Hospital of Xi'an Jiaotong University were retrospectively analyzed using univariate and multivariate logistic regression analysis. Results: In this study, the DGF incidence was 17.7% (20/113); The multivariate logistic regression results showed that terminal resistance (OR: 1.879, 95% CI 1.145–3.56) and glutathione S-transferase (GST)(OR = 1.62, 95% CI 1.23–2.46) were risk factors for DGF; The Cox model analysis indicated that terminal resistance was an independent hazard factor for renal function recovery time (HR = 0.823, 95% CI 0.735–0.981). The model combining terminal resistance and GST (AUC = 0.888, 95% CI: 0.842–0.933) significantly improved the DGF predictability compared with the use of terminal resistance (AUC = 0.756, 95% CI 0.693–0.818) or GST alone (AUC = 0.729, 95% CI 0.591–0.806). Conclusion: According to the factors analyzed in this study, the combination of HMP parameters and perfusate biomarkers displays a potent DGF predictive value.